Artur Mezglewski, Henryk Misztal, Piotr Stanisz, Prawo wyznaniowe, Warszawa 2006, Wydawnictwo C. H. Beck, ss. 284 - Borecki, Paweł (Zeszyty Prawnicze, 2017)
Artur Mezglewski, Henryk Misztal, Piotr Stanisz, Prawo wyznaniowe, Warszawa 2006, Wydawnictwo C. H. Beck, ss. 284